Fundamental of Entrepreneurship (ENT300) Hype Laundry Cafe / Rahman Hashim ...[et al.] - Hashim, Rahman; Abdul Khalik, Fazira; Abdul Rahman, Nurdiyya Arina; Sedik, Mohamad Haziq Iqbal; Mohd Fairul, Radikha (2015)
This business plan which includes full description about our company background, marketing plan, Operating plan, administration plan and financial plan is specially prepared for our lecturer, Miss Philomina Francis Banyie. Located at sublot 1, parent lots 3021, block 1, Samarahan land district, Jalan datuk mohd. musa, Kota Samarahan, Sarawak, Hype Laundry Cafe will be commence on 17 SEPTEMBER 2016 and was registered as companies form of business. Our Laundry cafe business hour will be operating 24 hours 7 days, from Monday to Sunday. Hype Laundry Cafe is a start-up business and our fully hope to have a chance to develops our business to be in same level with other successful laundry branches, such as International laundry. We choose laundry as our main product because, we can see that this kind of business have a chance to success in the future. In addition, we serve this business in the industries. This is because, nowadays, when involve in business or any discussion, other than company meeting room or office, some of the people might like to choose the outdoor places to get more wide observation about their business. This also helps them reduce their stress. Other than that, by cafe services, the family member or a group of friends also can spend their time at our cafe enjoying our product. Our cafe also provides, free Wi-Fi to the entire customer that spent their time in our cafe. Through this, we believe that, 'more time customer spent in our cafe, more products their purchase’. Lastly, the standard preparation needs to be prepared before commencing the business. All the major aspect of planning, organizing, leading and controlling the strategies have to be considered to ensure the proper management of the business in obtaining and achieving the goals of the company.